Opto-electronics engineering and materials research : selected, peer reviewed papers from the 2012 International Meeting on Opto-Electronics Engineering and Materials Research (OEMR2012), July 27-29, 2012, Shenyang, Liaoning, China - Liang, J. Y.; Li, D. G. (Advanced materials research ;, 2012)
These are the proceedings of the2012 International Meeting on Opto-Electronics Engineering and Materials Research (OEMR2012). The 149 peer-reviewed papers are grouped into 2 chapters: 1 - Materials Science and 2 - Opto-Electronics Engineering.